Functional characterization and in vitro screening of Fructobacillus fructosus MCC 3996 isolated from Butea monosperma flower for probiotic potential. (14th February 2020) - Patil, M.; Jadhav, A.; Patil, U.
Abstract: The fructophilic bacterium Fructobacillus fructosus MCC 3996 described in the present investigation was isolated from the nectar of Butea monosperma flower and evaluated in vitro for the manifestation of probiotic features. The strain utilizes fructose faster than glucose and is capable to grow in the range of 1–35% fructose concentration (optimum 5% w/v) and thus denotes its fructophilic nature. In vitro assessments of the strain have examined for the endurance in acidic environment/gastric juice, the better auto‐aggregation ability even in the presence of hydrolytic enzymes, co‐aggregation with pathogenic bacteria, hydrophobicity properties and no haemolytic activity to elucidate its feasible probiotic use. The significant antagonistic activity against several detrimental bacteria, despite lacking the bacteriocin secretion, is an astonishing feature. Owing to the indigenous origin of the isolate, it could be used as a probiotic, starter culture, and/or the active ingredient of food formulation may contribute to improve the desirable fermentation, long‐term storage and nutritional benefits of foods especially rich in fructose. Significance and Impact of the Study: This study provided in vitro evidence that Fructobacillus fructosus MCC 3996 have endurance in acidic gastric juice, better co‐aggregation, auto‐aggregation properties, splendid antagonistic activities against several bacteria involved in food spoilage/human infections, pertinent antibiotic susceptibility profile and no haemolytic activity. Also, F. fructosus have the capability to survive in the appreciable amount of fructose, and this advocates that the strain could be used as starter culture and/or the active ingredient of fructose‐rich foods. The current in vitro study provided a strong basis for further in vivo research to identify the health beneficial characteristics of F. fructosus and its potential could be effectively utilized as health‐boosting ingredient in food and pharmaceutical industries. Abstract : Significance and Impact of the Study: This study provided in vitro evidence that Fructobacillus fructosus MCC 3996 have endurance in acidic gastric juice, better co‐aggregation, auto‐aggregation properties, splendid antagonistic activities against several bacteria involved in food spoilage/human infections, pertinent antibiotic susceptibility profile and no haemolytic activity. Also, F. fructosus have the capability to survive in the appreciable amount of fructose, and this advocates that the strain could be used as starter culture and/or the active ingredient of fructose‐rich foods. The current in vitro study provided a strong basis for further in vivo research to identify the health beneficial characteristics of F. fructosus and its potential could be effectively utilized as health‐boosting ingredient in food and pharmaceutical industries.